Endobronchial optical coherence tomography helps to estimate the cartilage damage of the central airway in TBTB patients - Zong, Kaican; Liu, Bin; Li, Shiying; Li, Yishi; Guo, Shuliang (Frontiers in Cellular and Infection Microbiology, 2023)
Purpose At present, there are few examination methods used to evaluate tracheobronchial cartilage damage. In our study, we explored whether endobronchial optical coherence tomography (EB-OCT) can be used to estimate central airway cartilage damage in tracheobronchial tuberculosis (TBTB) patients. Methods In our study, we used the OCTICS Imaging system to perform EB-OCT scanning for TBTB patients. The thickness of the central airway wall and cartilage was measured by the OCTICS software system workstation. Results There were 102 TBTB patients included in our study cohort. Their EB-OCT images of the central airway cartilage showed that abnormal cartilage manifests as thinning of the cartilage, cartilage damage, cartilage destruction, and even cartilage deficiency. The cartilage morphology becomes irregular and discontinuous. Some parts of the cartilage become brighter in grayscale. The intima of the cartilage is thickened and discontinuous, and the boundary with submucosa and mucosa is unclear. Conclusion Our study conducted EB-OCT examination of the central airway cartilage of TBTB patients in vivo for the first time. EB-OCT helps to estimate the cartilage damage of the central airway in TBTB patients to some extent.